Medullary sponge kidney - the mysterious name of a simple disease - Bigosiński, Karol; Dubaj , Maciej; Dembowska , Aleksandra (Journal of Education, Health and Sport, 2022)
Medullary sponge kidney (renal spongiosis), (MSK) is a rare developmental anomaly of the kidney of unknown cause. It is presumed, that people with a genetic predisposition (<5% family occurrence) are prone to the disease. The peak of diagnosis is between the ages of 20-50, usually by chance (due to lack of symptoms) during an abdominal X-ray, where the so-called nephrocalcinosis (calcifications in the kidney) can be observed. Another radiologic test, that may suggest the condition in question is abdominal ultrasound, where cysts up to 8 mm in diameter in the medullary part of the kidney and calcifications can be seen. Diagnosis may also be based on the diagnosis of pre-existing stones and urinary tract infections, or hematuria. Urography has the highest sensitivity to sponge kidney. Symptoms, if already present, are characterized by low back pain, hematuria, hematuria, recurrent urinary tract infections, proteinuria, sterile purulence. Ultimately, the aforementioned pathologies can lead to kidney failure. To date, no causal treatment has been developed; only symptomatic treatment of lithiasis foci and urinary tract infections is possible. The purpose of the following paper was to describe the definition, epidemiology and etiology of MSK and to highlight the randomness of diagnosis and the problem in the lack of specific therapy for this renal developmental disorder. Current publications and guidelines from scientific societies around the world were reviewed, using MeSH-compliant keywords.